2014
DOI: 10.1016/j.cis.2013.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A bottom-up approach to understanding protein layer formation at solid–liquid interfaces

Abstract: A common goal across different fields (e.g. separations, biosensors, biomaterials, pharmaceuticals) is to understand how protein behavior at solid-liquid interfaces is affected by environmental conditions. Temperature, pH, ionic strength, and the chemical and physical properties of the solid surface, among many factors, can control microscopic protein dynamics (e.g. adsorption, desorption, diffusion, aggregation) that contribute to macroscopic properties like time-dependent total protein surface coverage and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 192 publications
2
58
0
Order By: Relevance
“…15,17 Some of the methods that can provide information on adsorbed protein orientation and tertiary (and quaternary) structure include fluorescence, [18][19][20][21] time-of-flight secondary-ion mass spectrometry, [22][23][24] nuclear magnetic resonance spectroscopy (NMR), 25,26 and amino acid labeling/mass spectrometry (AAL/MS). [27][28][29][30][31] Methods for the determination of secondary structure of adsorbed proteins include Fourier transform infrared spectroscopy, 32,33 surface enhanced Raman scattering, 34,35 and circular dichroism spectropolarimetry (CD).…”
Section: Introductionmentioning
confidence: 99%
“…15,17 Some of the methods that can provide information on adsorbed protein orientation and tertiary (and quaternary) structure include fluorescence, [18][19][20][21] time-of-flight secondary-ion mass spectrometry, [22][23][24] nuclear magnetic resonance spectroscopy (NMR), 25,26 and amino acid labeling/mass spectrometry (AAL/MS). [27][28][29][30][31] Methods for the determination of secondary structure of adsorbed proteins include Fourier transform infrared spectroscopy, 32,33 surface enhanced Raman scattering, 34,35 and circular dichroism spectropolarimetry (CD).…”
Section: Introductionmentioning
confidence: 99%
“…The results vary with the experimental setups (variable surface area and chemistry), the timescales, and the sensitivities of the respective techniques, and it remains challenging to compare different studies. For proteins, there are different models describing their adsorption/desorption behavior at interfaces, 31 the most widely known being the Langmuir model and the random sequential adsorption model. However, these models have two main limitations: 31 first, the equilibrium hypothesis does not apply as desorption experiments generally lead to a residual, irreversibly bound protein fraction and desorbed proteins can potentially readsorb at the surface.…”
Section: Surface-adsorbed Amountmentioning
confidence: 99%
“…For proteins, there are different models describing their adsorption/desorption behavior at interfaces, 31 the most widely known being the Langmuir model and the random sequential adsorption model. However, these models have two main limitations: 31 first, the equilibrium hypothesis does not apply as desorption experiments generally lead to a residual, irreversibly bound protein fraction and desorbed proteins can potentially readsorb at the surface. Second, these models do not account for interactions between surface-adsorbed molecules such as rearrangements with increasing surface coverage.…”
Section: Surface-adsorbed Amountmentioning
confidence: 99%
“…For instance, single molecule tracking experiments have given more detailed insights into the kinetics of proteins at interfaces. 10 Individual particle tracking has shown that protein-protein interactions and protein conformation can change the residence time of proteins on the interfaces and enhance clustering on the interface. 11,12 The effect of particle shape supports previous studies that fit protein surface coverage experiments to kinetic models of non-spherical molecules.…”
Section: Introductionmentioning
confidence: 99%